2005
DOI: 10.1055/s-2005-871867
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Pharmacologic Agents Used In Catheter-Directed Thrombolysis

Abstract: The use of catheter-directed thrombolysis is a proven treatment for arterial ischemia, deep vein thrombosis, and severe pulmonary embolism. For arterial ischemia, thrombolysis has resulted in improved amputation-free survival and fewer subsequent surgeries to reestablish blood flow to the ischemic limb. The management of patients with thromboembolic diseases is complex, and the multiple thrombolytic drugs available to choose from compound this complexity. Although some believe the available thrombolytic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Surgical approaches tend to be associated with more serious complications such as infection, as well as risks of anaesthesia. 15,16) This has resulted in endovascular approaches largely replacing surgical ap- proaches and thus being recommended as the first line of treatment in thrombosed AVFs today. 4) We have achieved a technical success rate of 92% ( Table 2), which is consistent with the rates (90% or better) reported in the National Kidney Foundation Dialysis Outcomes Quality Initiative (NKF KDOQI) guidelines for stenosed and occluded AVFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical approaches tend to be associated with more serious complications such as infection, as well as risks of anaesthesia. 15,16) This has resulted in endovascular approaches largely replacing surgical ap- proaches and thus being recommended as the first line of treatment in thrombosed AVFs today. 4) We have achieved a technical success rate of 92% ( Table 2), which is consistent with the rates (90% or better) reported in the National Kidney Foundation Dialysis Outcomes Quality Initiative (NKF KDOQI) guidelines for stenosed and occluded AVFs.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approaches tend to be associated with more serious complications such as infection, as well as risks of anaesthesia. 15 , 16 ) This has resulted in endovascular approaches largely replacing surgical approaches and thus being recommended as the first line of treatment in thrombosed AVFs today. 4 )…”
Section: Discussionmentioning
confidence: 99%
“…The recommended dose ranges for the commonly used thrombolytic agents are 80,000–120,000 IU/h of urokinase or 0.2–0.5 mg/h of r-tPA. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…One important concept introduced by Swischuk and Smouse to explain this discrepancy is that a distinction should be made of two separate processes: fibrinolysis-the breakdown of crosslinked fibrin and fibrinogenolysis-the breakdown of freely circulating fibrinogen. 23 tPA, like other lytic agents, causes fibrinolysis that involves the breakdown of fibrin into fibrin degradation products (FSPs). One moiety of FSPs subsequently enters the circulation and functionally serves to stimulate tPA activation of systemic plasminogen to plasmin, which in turn breaks down further fibrin.…”
Section: Complicationsmentioning
confidence: 99%
“…Swischuk and Smouse (2005) demonstrated that using tPA in doses greater than 1.5 mg/h in conjunction with full heparinization led to higher rates of major bleeding. 23,25 Their subsequent report in a nonrandomized dose ranging study demonstrated that using lower doses of tPA as outlined earlier with subtherapeutic heparinization significantly reduced bleeding. Therefore, the newer fibrinspecific agents such as tPA should be used with caution because they have a relatively narrower window of dosing safety.…”
Section: Complicationsmentioning
confidence: 99%